Galaxy formation and evolution from deep optical and infrared surveys - Adams, N (2021)
In this thesis, I present results from population studies conducted on galaxies across most of cosmic time. Using the unique depth and area combination of modern, ground-based surveys allows for strong constraints to be placed on the number density of the most massive and luminous galaxies between redshifts of 0.1<z<5.2, while simultaneously allowing for contextualisation of results with the fainter/lower-mass population. The dataset compiles together ~ 2,000,000 objects over 6 square degrees of the sky and I use these to tackle two issues facing extragalactic research.